(untitled) (Ex Chordis, 2023)
In the last twenty years, music performance analysis has been evolving from various perspectives. To the traditional ethnomusicological approach, oriented to non-European musical traditions, the recent performance studies have been led to investigate the creative process of music performance in Western music tradition. This causes the emergence of the performative turn and the artistic turn in music performance analysis and the origin of artistic research in music. But what are the approaches of music performance analysis specifically in relation to the research questions, objectives, methods and results of artistic research in music? This article offers an overview of the different approaches in the investigation of music performance in the context of artistic research in music, in particular methods for the music performance analysis of a written composition. By defining the path that determines the transformation of music practice into a research on music performance, divergences and convergences of the methodological approach in artistic research will be pointed out in comparison to the methodological approach in scientific research. Therefore, the objectives of artistic research in music and a mixed method (that integrates a performative analysis and empirical analysis) will be presented. The application of digital technology for the documentation and analysis of performers’ gestures will be a topic of discussion to bring out the potential of the dialogue between art, science and technology in the investigation of music performance analysis in artistic research.